2010
DOI: 10.1111/j.1440-1819.2010.02076.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Z‐scores of VSRAD and regional cerebral blood flow of SPECT in patients with Alzheimer's disease and mild cognitive impairment

Abstract: Aims:The purpose of the present study was to investigate whether there were correlations between atrophy of the entorhinal cortex and individual regional cerebral blood flow (rCBF) in patients with Alzheimer's disease (AD) and amnestic mild cognitive impairment (MCI) to better clarify the relationships between morphological and functional changes in AD.Methods: Twenty-six patients including sixteen AD and 10 amnestic MCI patients were enrolled. Z scores of voxel-based specific regional analysis system for AD (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…SPECT showed diminished blood flow to the parietal lobes bilaterally, and the hippocampus had become atrophic. Her Z score of VSRAD was 3.2 [3]. Thus, she was suspected of having AD, and we prescribed donepezil hydrochloride.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SPECT showed diminished blood flow to the parietal lobes bilaterally, and the hippocampus had become atrophic. Her Z score of VSRAD was 3.2 [3]. Thus, she was suspected of having AD, and we prescribed donepezil hydrochloride.…”
Section: Resultsmentioning
confidence: 99%
“…The Z score of VSRAD was 1.33, so AD was interpreted as negative [3]. However, the level of Aβ40 was 2,430 pmol/l, Aβ42 was 155 pmol/l and t-tau was 645 pg/ml in CSF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The VSRAD analysis revealed that Z-scores indicating probable AD and amnestic MCI patients averaged 1.94 ± 1.24 (ranging from 0 to 4.69) [22]. Subjects exhibiting MTA-ERC atrophy as well as probable AD were included in the present MCI study.…”
Section: Discussionmentioning
confidence: 99%
“…The VSRAD has been shown to achieve high accuracy (87.8%) in discriminating patients in the very early stages of AD with MCI from normal control subjects using Z-scores [21]. Atrophy of the MTA-ERC was indicated by VSRAD to exhibit a clear functional relationship with blood flow changes in the hippocampus, thalamus and temporal lobe, which were suggested to be closely related to inter-regional anatomical and physiological connections [22]. In cognitive function, Nagata et al [23] reported that Z-scores of the VSRAD was associated with executive function, although there was no relationship between Z-scores and memory function which was assessed by the Mini-Mental State Examination (MMSE) in the amnestic MCI and early AD patients.…”
Section: Introductionmentioning
confidence: 99%